Redesain Struktur atas Jembatan Kedungsoko Tulungagung Menggunakan Gelagar Prategang - Dimas Aryasena Praditya (Fakultas Teknik, 2024)
The upper structure design of Kedungsoko Bridge features a steel frame with a Railway type. Spanning 45 meters wide and 7 meters across, the bridge's limited height and width, attributed to the steel frame system, pose challenges for wide and higher load transportation. Situated in the Tulungagung District, Tulungagung Regency, East Java, it connects Kedungsoko Subdistrict and Waung Village, separated by the Ngrowo River. The bridge underwent a redesign, extending its length to 45 meters and width to 8 meters. Load planning for the bridge adheres to the latest regulations, specifically SNI 1725 (2016) and SNI 2833 (2016). The planning methodology follows Practical Guidelines for Bridge Technical Planning No. 02/M/BM/2021, supplemented by other bridge regulations such as RSNI T 12 (2004) and SNI 2847 (2019). The analysis process involves utilizing SAP2000 v22 software and Microsoft Excel. The design incorporates WIKA Beton's Girder-I H-210 product, spaced at 1800 mm intervals, with a strength of f'c = 50 MPa. This necessitates the use of 4 tendons per girder, totaling 73 uncoated 7 wire strands ASTM A-416 grade 270 for each girder. Additionally, the floor slabs are 0.20 meters thick with a 5 cm overlay.
Reaploud Repository February_Hasyim
Keywords: Bridge; Presress; PC I Girder